KESIAPAN DAN INOVASI SUMBER DAYA MANUSIA SMA PLUS AL GHIFARI DALAM IMPLEMENTASI MERDEKA BELAJAR - Masduqi, Masduqi; Karnita Soleha, Lilis (Universitas Muhammadiyah Palembang, 2024)
Purpose- This research explores the readiness and innovation of human resources in the implementation of the Freedom to Learn (Merdeka Belajar) initiative at SMA Plus Al Ghifari. The study aims to answer three main questions is what readiness is needed by students and educators in adapting to the flexible curriculum and technological advancements? what are the inhibiting factors affecting the readiness and innovation of human resources in implementing Freedom to Learn? and what efforts can be made to overcome these inhibiting factors? Design/methodology- The research employs a mixed-methods quallitatif interviews, and document analysis. The research involved three main participant groups, namely Principals, Teachers, as well as secondary data obtained from employees in technical and operational technical and administrative units. Finding- The findings in this reaseacrch is the priority is the development of teachers' skills in designing competency-based learning and supporting innovation. Hindering factors such as inadequate infrastructure and technology, resistance to change, and the inability to adapt to the new curriculum need to be overcome. Steps such as investing in improving infrastructure, training and skill development, as well as increasing awareness and motivation, need to be implemented immediately through internal socialization and campaigns